Evelin Underhill ‒ Mysticism as the Art of Being in Relationship with the Absolute - Pawłowski, Kazimierz (Filozofia Chrześcijańska, 2025)
The text attempts to outline the spiritual profile of Evelin Underhill, an English mystic from the first half of the 20th century, on her journey to introduce mysticism into the everyday life of Christians, that is, to make mystical spirituality a crucial element of the practical Christian life. The main determinant of spirituality thus understood is its orientation, and with it the practical Christian life, toward the Absolute. This orientation gives meaning to the Christian’s life and influences their life choices.